Potential Value of Matrix Metalloproteinase-13 as a Biomarker for Osteoarthritis - Xin, Xing; Tan, Qizhao; Li, Fang; Chen, Zhongqiang; Zhang, Ke; Li, Feng; Yang, Bin; Xing, Zhili; Zhou, Fang; Tian, Yun; Lv, Yang; Zhu, Tengjiao (Frontiers in Surgery, 2021)
Background: Emerging knowledge has highlighted the role of matrix metalloproteinase (MMP)-13 in osteoarthritis (OA); however, the suitability of MMP-13 as a biomarker for OA remains unclear. Therefore, this study investigated the potential value of MMP-13 as a clinically applicable biomarker for OA. Methods: The study enrolled 51 patients, of which 33 had advanced varus OA and 18 did not have OA. Immunohistochemistry and western blotting analyses were performed to measure MMP-13 activity in the cartilage and subchondral bone of patients with OA. Enzyme-linked immunosorbent assay was used to measure serum MMP-13 levels in patients with or without OA. The association between serum MMP-13 levels and clinical symptoms was assessed using the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC). Radiological severity was assessed using the Kellgren–Lawrence (KL) grading system. Proportional odds logistic regression models were used to assess serum MMP-13 levels as a potential predictor for OA. Results: Serum MMP-13 levels were significantly higher in the severe-wear cartilage of the medial tibial plateau than in the relatively intact portion of the lateral cartilage (p < 0.05). This was contrary to the findings for MMP-13 differential expression in the subchondral bone in knee OA (p < 0.05). Serum MMP-13 levels differed significantly between patients with and without OA. We found remarkable associations among serum MMP-13 levels, WOMAC scores, and KL grading scores. Furthermore, subsequent analysis revealed that serum MMP-13 level was a significant predictor for OA. Conclusion: MMP-13 is valuable for diagnosing OA, measuring disease severity, and predicting OA. Serum MMP-13 levels can serve as a potential biomarker for knee OA.